Lobe Variation Effects of Experimental Diabetes and Insulin Replacement on Rat Prostate - Porto, Elaine Manoela; De Alcantara Dos Santos, Sergio Alexandre [UNESP]; Ribeiro, Larissa Mayumi [UNESP]; Lacorte, Livia Maria [UNESP]; Rinaldi, Jaqueline Carvalho [UNESP]; Justulin, Luis Antonio; Felisbino, Sergio Luis [UNESP] (Wiley-Blackwell, 2011)
We investigated the impact of diabetes with simultaneous and late insulin replacement on rat prostate growth during puberty, paying special attention to different prostatic lobes. Diabetes was induced by administration of streptozotocin (STZ) in 40-day-old male Wistar rats. A subset of diabetic rats underwent simultaneous insulin replacement (3 days after STZ administration), and another subset underwent a late insulin replacement (20 days after STZ administration). The ventral, dorsolateral, and anterior prostatic lobes were weighed and processed for histological, immunohistochemical, and morphometric analyses. Both diabetic and insulin-treated animals maintained low plasma testosterone (T) concentrations, whereas dihydrotestostenore (DHT) levels were normal. Diabetic animals had a decreased gain in absolute prostatic weight when compared to age-matched controls and insulin replacement animals. However, prostatic lobe weight in the diabetic animals was similar to 100% higher, even at the beginning of the experiment. Among the lobes, the anterior lobe showed the highest weight gain in diabetic and insulin replacement conditions. Epithelial cell proliferation in all lobes was significantly reduced in diabetic animals and significantly increased in insulin replacement animals, although apoptosis was unaltered. In conclusion, diabetes diminishes, but does not abolish, prostate growth during puberty. Even late insulin administration reduces the adverse effects of this disease on the prostate. In a scenario with both low insulin and T levels, DHT and other factors may play an important role in pubertal prostate growth. The adverse effects of diabetes on the rat prostate show a variation in lobe response, suggesting that diabetes may affect human prostate zones differently. Microsc. Res. Tech. 74:1040-1048, 2011. (C) 2011 Wiley Periodicals, Inc.
Keywords: prostate; diabetes; cell proliferation; apoptosis; insulin